Development of Potential of Biogas Waste and Cow Urine for Organic Liquid Fertilizer - Mujiyono Mujiyono; Sujangi Sujangi; Beny Suyanto (Alliance oh Health Activists (AloHA), 2021)
Biogas waste (slurry) and cow urine can be processed into fertilizer that has economic value for the community in addition to making the cowshed cleaner. This study aims to process biogas waste and cow urine into organic liquid fertilizer. This experimental study used a randomized design consisting of 5 formulations of organic liquid fertilizer that were treated, namely the ratio of biogas waste and cow urine with a ratio of formula: A (3:1); B (1:1); C (2:1); D (1:0) and E (0:1). Each treatment was replicated 3 times, in order to obtain 15 samples. To speed up the process of making fertilizer, 1% EM4 was added. The process of making fertilizer using aeration and fermentation methods. Assessment of fertilizer maturation results based on physical and chemical parameters. The results of the measurement of chemical parameters are: N (1.03%-1.51%), P (0.78%-1.22%); K (0.15%-4.51%) and C/N ratio (13.9-23.0). The best ratio of biogas waste and urine is 1:1. The results of the measurement of physical parameters are: characteristic odor of fermentation/tape; pH (7.0-8.6); color/texture: dark brown; and this does not violate the limits of the minister of health regulations. Keywords: biogas waste; cow urine; liquid organic fertilizer